Feedback Activation of STAT3 as a Cancer Drug-Resistance Mechanism. (January 2016) - Zhao, Chengguang; Li, Huameng; Lin, Huey-Jen; Yang, Shulin; Lin, Jiayuh; Liang, Guang
Abstract : Signal transducer and activator of transcription 3 (STAT3) plays crucial roles in several cellular processes such as cell proliferation and survival, and has been found to be aberrantly activated in many cancers. Much research has explored the leading mechanisms for regulating the STAT3 pathway and its role in promoting tumorigenesis. We focus here on recent evidence suggesting that feedback activation of STAT3 plays a prominent role in mediating drug resistance to a broad spectrum of targeted cancer therapies and chemotherapies. We highlight the potential of co-targeting STAT3 and its primary target to overcome drug resistance, and provide perspective on repurposing clinically approved drugs as STAT3 pathway inhibitors, in combination with the FDA-approved receptor tyrosine kinase (RTK) inhibitors, to improve clinical outcome of cancer treatment. Trends: The efficacy of RTK-targeted therapies is limited by the development of drug resistance. Inhibition of various receptor tyrosine kinases (RTK) such as EGFR, MEK, FGFR, and HER2 could trigger feedback activation of STAT3. Feedback activation of STAT3 is a common cause of resistance to many targeted cancer therapies and chemotherapies. Combination therapy with a RTK inhibitor and a selective STAT3 inhibitor exerts synergistic effects to overcome drug resistance.